THE ANALYSIS OF “BOAT STEALING” EXTRACT FROM “THE PRELUDE” BY WILLIAM WORDSWORTH - Kurbonova , Nodira Rozikovna; Anvarova, Umidabegim Ja’farovna (Innovative Development in Educational Activities, 2023)
The article analyzes one extract from the autobiographical poem “The Prelude” by a romantic writer William Wordsworth. For hundreds of years, poets and writers have written about mankind’s relationship with nature. While some believe that we have control over nature and can manipulate it to our advantage, others believe that we are at the mercy of nature, which is a powerful and terrifying force. Others, on the other hand, have seen man’s relationship with nature as one of serene tranquillity, which allows a man to gather himself and feel one with his environment.